A Basal Lithostrotian Titanosaur (Dinosauria: Sauropoda) with a Complete Skull: Implications for the Evolution and Paleobiology of Titanosauria. - Rubén D F Martínez; Matthew C Lamanna; Fernando E Novas; Ryan C Ridgely; Gabriel A Casal; Javier E Martínez; Javier R Vita; Lawrence M Witmer (PLoS ONE, 2016)
We describe Sarmientosaurus musacchioi gen. et sp. nov., a titanosaurian sauropod dinosaur from the Upper Cretaceous (Cenomanian-Turonian) Lower Member of the Bajo Barreal Formation of southern Chubut Province in central Patagonia, Argentina. The holotypic and only known specimen consists of an articulated, virtually complete skull and part of the cranial and middle cervical series. Sarmientosaurus exhibits the following distinctive features that we interpret as autapomorphies: (1) maximum diameter of orbit nearly 40% rostrocaudal length of cranium; (2) complex maxilla-lacrimal articulation, in which the lacrimal clasps the ascending ramus of the maxilla; (3) medial edge of caudal sector of maxillary ascending ramus bordering bony nasal aperture with low but distinct ridge; (4) 'tongue-like' ventral process of quadratojugal that overlaps quadrate caudally; (5) separate foramina for all three branches of the trigeminal nerve; (6) absence of median venous canal connecting infundibular region to ventral part of brainstem; (7) subvertical premaxillary, procumbent maxillary, and recumbent dentary teeth; (8) cervical vertebrae with 'strut-like' centroprezygapophyseal laminae; (9) extremely elongate and slender ossified tendon positioned ventrolateral to cervical vertebrae and ribs. The cranial endocast of Sarmientosaurus preserves some of the most complete information obtained to date regarding the brain and sensory systems of sauropods. Phylogenetic analysis recovers the new taxon as a basal member of Lithostrotia, as the most plesiomorphic titanosaurian to be preserved with a complete skull. Sarmientosaurus provides a wealth of new cranial evidence that reaffirms the close relationship of titanosaurs to Brachiosauridae. Moreover, the presence of the relatively derived lithostrotian Tapuiasaurus in Aptian deposits indicates that the new Patagonian genus represents a 'ghost lineage' with a comparatively plesiomorphic craniodental form, the evolutionary history of which is missing for at least 13 million years of the Cretaceous. The skull anatomy of Sarmientosaurus suggests that multiple titanosaurian species with dissimilar cranial structures coexisted in the early Late Cretaceous of southern South America. Furthermore, the new taxon possesses a number of distinctive morphologies-such as the ossified cervical tendon, extremely pneumatized cervical vertebrae, and a habitually downward-facing snout-that have rarely, if ever, been documented in other titanosaurs, thus broadening our understanding of the anatomical diversity of this remarkable sauropod clade. The latter two features were convergently acquired by at least one penecontemporaneous diplodocoid, and may represent mutual specializations for consuming low-growing vegetation.